Interrogating the nexus between irregular migration and insecurity along 'ungoverned' border spaces in West Africa. Issue 3 (3rd July 2021) - Aniche, Ernest Toochi; Moyo, Inocent; Nshimbi, Christopher Changwe
ABSTRACT: The 'coloniality', porosity, and 'ungovernability' of borders in West Africa, have engendered undocumented migration, in which most people engage to visit their kin and for economic reasons such as herding, farming, fishing, hunting, and trading. This occurs concurrently with human smuggling, human trafficking, gun-running, terrorism, and money laundering. The rise in these cross-border criminal activities and the resultant insecurity have put irregular migration into the mainstream of political and academic conversation, generating national, regional, and global concerns. Against this backdrop, this paper examines the nexus between irregular migration and insecurity along 'ungoverned' borders in West Africa, based on a review of relevant literature on migration, security, and governance in scholarly journals, books as well as relevant reports, newspaper, and media accounts. The overarching question which this raises and is addressed in this paper is: How does the coloniality and porosity of ungoverned borders in West Africa engender and/or entrench cross-border insecurity? Addressing this question suggests the need to provide sufficient governance mechanisms that involve both state and non-state actors in order to reduce the ungoverned spaces in this part of Africa.